2005
DOI: 10.1590/s0100-879x2005000500001
|View full text |Cite
|
Sign up to set email alerts
|

The modest but growing Brazilian presence in psychiatric, psychobiological and mental health research: assessment of the 1998-2002 period

Abstract: The objective of the present survey was to assess the Brazilian scientific production in psychiatry, psychobiology, and mental health during the 1998-2002 period. The universities' graduate programs concentrate the vast majority of the scientific production in Brazil. We assessed the annual reports from the graduate programs to the Brazilian Ministry of Education concerning master's and doctoral theses and the articles published in journals indexed by the Institute of Scientific Information (ISI). There are ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 11 publications
0
40
1
10
Order By: Relevance
“…Recentemente, diversos estudos vêm tentando caracterizar quantitativamente e qualitativamente a produção científica brasileira, principalmente no cenário internacional [1][2][3][4][5][6][7][8] . A produção científica brasileira, de forma geral, apresentou um crescimento de quatro vezes, desde a década 1980, no que se refere ao total de artigos publicados.…”
Section: Discussionunclassified
“…Recentemente, diversos estudos vêm tentando caracterizar quantitativamente e qualitativamente a produção científica brasileira, principalmente no cenário internacional [1][2][3][4][5][6][7][8] . A produção científica brasileira, de forma geral, apresentou um crescimento de quatro vezes, desde a década 1980, no que se refere ao total de artigos publicados.…”
Section: Discussionunclassified
“…2 Brazil has been ranked as the 29 th most productive country in the world, in relation to psychiatry and psychology, and the first among Latin American countries, according to the Institute for Scientific Information/ Thomson Scientific (ISI). Moreover, the mean number of citations per paper attained by Brazilian papers (5.4), which is the highest in Latin America, is not too far behind some developed countries like France (6.3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mean number of citations per paper attained by Brazilian papers (5.4), which is the highest in Latin America, is not too far behind some developed countries like France (6.3). 2 A comparison of the number of ISI publications in psychiatry between the periods 1981-1985 and 1991-1995 demonstrated that there was a remarkable 168% increase in Brazilian production between these periods. 6 When these data were compared with the period 1999-2003, the number of publications increased further, from 110 to 496.…”
Section: Introductionmentioning
confidence: 99%
“…The same is true of Portuguese as there are fewer readers than English articles, thus restricting the audience and potential citations (Ariza & Granados, 2012). However, the lack of citations has also been attributed to the difficulty in accessing full text Latin American articles (Bressan, Gerolin, & Mari, 2005).…”
Section: Discussionmentioning
confidence: 99%